Mean global field power is reduced in infantile epileptic spasms syndrome after response to vigabatrin - Nair, Arjun; Ewusie, Joycelyne; Pentz, Rowan; Whitney, Robyn; Jones, Kevin (Frontiers in Neurology, 2024)
Purpose: Infantile epileptic spasms syndrome (IESS) is associated with abnormal neuronal networks during a critical age of synaptogenesis and brain plasticity. We hypothesized that computational and visual EEG biomarkers of IESS change in a correlated manner after treatment with Vigabatrin and that these responses may differ between responders and non-responders. Methods: A retrospective analysis of health records was conducted at a single center, involving children with IESS at initial diagnosis and following first-line treatment with Vigabatrin. Visual EEG biomarkers of hypsarrhythmia were compared to computational EEG biomarkers, including spike and spike fast-oscillation source coherence, spectral power and mean global field power, performed retrospectively on EEG recorded at initial diagnosis and post vigabatrin treatment. Responders and non-responders were compared in terms of their follow-up EEGs. Results: In this pilot study, we observed a significant reduction in the EEG biomarker of hypsarrhythmia/modified hypsarrhythmia from 20/20 (100%) at the initial diagnosis to 9/20 (45%) after treatment with vigabatrin indicating a 55% (11/20) responder rate. No significant difference in spike frequency was observed after treatment (p = 0.104). We observed no significant differences after treatment with vigabatrin in the computational EEG biomarkers that we assessed including spike source coherence at 90% (p = 0.983), spike source coherence lag range (p>0.999), spike gamma source coherence at 90% (p = 0.177), spike gamma source coherence lag range (p>0.999), spectral power (0.642), or mean global field power (0.932). However, when follow-up EEGs were compared, there was a significant difference in the mean global field power (p=0.038) between vigabatrin responders and non-responders. In contrast, no such difference was seen with respect to Spike Source Coherence at 90% (p = 0.285), spike course coherence lag range (p = 0.819), spike gamma source coherence at 90% (p = 0.205), spike gamma source coherence lag range (p>0.999), or spectral power (p=0445). Lastly, our treated group did not differ significantly from healthy controls at initial diagnosis and follow-up in terms of spectral power (p = 0.420) and mean global field power (0.127). Conclusion: Mean global field power is a computational EEG biomarker that is significantly reduced in IESS after treatment with vigabatrin.